THE INFLUENCE OF PRODUCTION COSTS ON NET PROFIT (Case Study on Automotive and Component Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2019) - Dick Wolters Marbun; Bill Schara Marbun (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2021)
This study aims to determine the effect of production costs on net income in automotive and component sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2019. The sample in this study is the automotive and component sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The sampling method used in this study is purposive sampling with a sample of 33 samples consisting of manufacturing companies in the automotive and component sub-sectors on the Indonesia Stock Exchange for the last 4 years. This study uses descriptive statistical methods, correlation coefficient analysis, coefficient of determination analysis, simple linear regression, and significance test (t test). This study uses data from the annual financial reports of automotive and component sub-sector companies listed on the Indonesia Stock Exchange in 2016-2019. The secondary data was processed using SPSS. The results of the study show that production costs have a significant effect on net income.